Determination of Ilaprazole and Domperidone in Individual Dosage form Tablets by RP-HPLC - Suneetha, G.; Venkateswarlu, P.; Prasad, P.S.S.; Murali Krishna, P. (Asian Journal of Chemistry, 2013)
A simple, sensitive and precise high performance liquid chromatographic method for the analysis of ilaprazole and domperidone has been developed, validated and used for the determination of compounds in commercial pharmaceutical products. The compounds were well separated an isocratically on a C18 column inertisil C18, 5 μm, [250 mm × 4.6 mm] utilizing a mobile phase consisting of acetonitrile: phosphate buffer (60:40, v/v, pH 7.0) at a flow rate of 1.0 mL/min with UV detection at 243 nm. The retention time of ilaprazole and domperidone was found to be 2.543 min and 7.245 min, respectively. The method was found selective and peaks of ilaprazole and domperidone were well separated. The proposed method is linear (r2 = 0.999 for ilaprazole and domperidone), accurate with 99.5 % recovery for ilaprazole and 99.4 % recovery for domperidone and precise (% RSD < 1 %). The method has been used to determine potency of commercial product and potency was found within limit. The method can be used for the analysis of ilaprazole and domperidone in tablet dosage form.